Physical-mathematical model for determination of variation of internal forces in the simplified analysis of a beam (2021)
. Springs are often taught in subjects of physics such as statics and solid mechanics belonging to civil engineering programs and mechanical engineering. This knowledge can be applied successfully in the modeling of structures and the consequent development of structural analysis. This paper presents the results of an investigation on physic-mathematical models which uses springs to replace complex connective conditions attempting to simplify the structural analysis process. The work focuses on the analysis of beams supported upon masonry walls, applying variations to the span lengths, sections and loads on them and considering realistic variations of the stiffness conditions required in the supports to meet the demands that these variations impose. For this, continuous beams with two spans with three types of section that are supported by walls that support different levels of restriction from different heights of the building of which they are part are modeled. It is concluded that there is an important influence of the slenderness of the beams and the degree of confinement of the supports upon the precision of the simplified model.